Quantum mechanics - Rae, Alastair I. M. (CRC Press, 2016)
Continuing to offer a clear, up-to-date treatment of the subject, this sixth edition explains the concepts of quantum mechanics for undergraduate students in physics and related disciplines and provides the foundation necessary for other specialized courses